THE CONCEPT OF DARK TOURISM, VISITORS’ MOTIVATION AND THE ENTAILED DISSONANCE IN SITES REPRESENTATION - Mavragani, Eleni; Mandrinou, Evangelia (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
The purpose of this research is to explore the concept of dark tourism, focusing on the conceptual approach of dark tourism, the different terms stated for its nature, the review of its historical background as well as its main categories. Emphasis is placed on the identification of the tourists’ general beliefs regarding the concept of dark tourism, their emotions related to visits to specific dark tourism monuments and the internal motives that serve as driving forces for visits to dark tourism spots of interest. The study investigates whether the contemporary representation of dark tourism monuments in Greece accurately reflects the historical background and the horrific events that took place in the past. The research aims to investigate whether there is a statistically significant correlation between the variables of dissonance in the representation of the sites, the motives and emotions of the tourists, and whether there is a statistical difference in the dissonance, emotions and motives based on the demographic results. The type of the research implemented is the primary quantitative research and the outcomes reveal that the overall picture of emotions is at an average level, with dark tourism eliciting both positive and negative emotions from the tourism audience.